Pengaruh Persepsi Kegunaan, Persepsi Kemudahan Penggunaan, Pengetahuan Akuntansi dan Kompatibilitas terhadap Minat UMKM dalam Menggunakan Aplikasi SI APIK - Kadek Wiratama; Ni Luh Gede Erni Sulindawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The purpose of this study is to determine the effect of perceived usefulness, perceived ease of use, accounting knowledge and compatibility on behavioural intention in using SI APIK applications by the MSMEs. This study uses a quantitative research design that used data collection instrument in the form of a questionnaire. The population that used in this study is all the MSMEs in Buleleng District. Determination of the sample is using the purposive sampling method and then calculated by using the Slovin formula for the minimum number of samples that needed, which resulted 98 samples from the total of 6.836 MSMEs. Data analysis that used in this study are descriptive analysis, variable measurement, data quality test, classic assumption test, multiple linear regression analysis and hypothesis test by using the SPSS application. The result of this study get that the perceved usefulness, perceived ease of use, and compatibility have positive and significant effect on behavioural intention in using the SI APIK application. While accounting knowledge has no positive and significant effect on behavioural intention in using the SI APIK application.